Plasmon induced enhanced photocatalytic activity of gold loaded hydroxyapatite nanoparticles for methylene blue degradation under visible light. Issue 14 (27th January 2017) - Mondal, Sudip; De Anda Reyes, Ma. E.; Pal, Umapada
Abstract : A facile surfactant free wet-precipitation process was employed to prepare hydroxyapatite (HAp) nanoparticles. Abstract : A facile surfactant free wet-precipitation process was employed to prepare hydroxyapatite (HAp) nanoparticles. Further, a microwave-assisted hydrothermal process was used to synthesize gold-loaded HAp (Au–HAp) nanocomposites with different Au contents. The nanocomposites of mesoporous structures exhibited a high specific surface area. Incorporated gold in the nanocomposites formed Au nanoparticles at the surface of HAp nanoparticles. Apart from characterizing the nanocomposites for their morphology, crystallinity, structural phase and optical behaviors, they were tested for photocatalytic degradation methylene blue under visible-light. Incorporation of Au nanoparticles significantly improved the photocatalytic activity of HAp nanoparticles under visible light irradiation. Fourier transformed infrared (FTIR) spectroscopy analysis confirmed the chemical stability of the catalyst under strong photo-induced oxidation-reaction. The strong dye adsorption capacity of HAp and surface plasmon resonance (SPR) of Au nanoparticles in the visible wavelength range make this novel Au–HAp nanocomposite an effective visible light photocatalyst for the degradation and adsorption of organic dye from their aqueous solutions. Being HAp a nontoxic, bioactive material and gold a nontoxic noble metal, the composite has the potential for utilization as ambiental friendly photocatalyst for wastewater treatment.